The Study of Liquid Waste Management in the Marine Product Processing Industry (Case Study of PT Bumi Menara Internusa Lamongan) - Durrotun Nafisah; Dewi Liesnoor Setyowati; Eva Banowati; Agustinus Sugeng Priyanto (International Conference on Science, Education, and Technology, 2021)
Lamongan regency has direct lines physical boundaries with coastal lines with potential sea waters and pond waters. The fishing industry is one of the fastest-growing industries in Lamongan District. Rapidly growing industrial activities cause environmental pollution caused by industrial waste disposal. This research aims to find out the process of liquid waste treatment processed through WWTP (Wastewater Treatment Plant) and analyze the quality standards of wastewater treatment plant effluent. Data collection techniques are conducted through interviews, observations, and documentation. PT Bumi Menara Internusa Lamongan has a conventional Suspended Solid Wastewaters Installation System which is aerobic decomposition that oxidizes organic materials into CO2, H2O, and NH4. Standard Wastewaters Quality Standard PT. Bumi Menara Internusa Lamongan refers to The Governor of East Java Regulation No. 72 of 2013 concerning Wastewater’s quality standards for the industry and /or Other Business Activities. Liquid waste treatment process through stages (1) Screener (filtration stage), (2) Equalization (decomposition stage), (3) Stabilization (Stabilization stage), (4) Clarifier (separation process between microorganisms and water treatment), and (5) evaluation (liquid waste worth exhausts or not). The results of the quality check effluent Wastewater Treatment Plant found no deviations in the results of effluent that exceeded the quality standards. Liquid waste that has been processed allows it to be used to water plants.